Bioactive contents, In vitro antiradical, antimicrobial and cytotoxic properties of rhubarb (Rheum ribes L.) extracts - Keser, Serhat; Keser, Fatma; Karatepe, Mustafa; Kaygili, Omer; Tekin, Suat; Turkoglu, Ismail; Sandal, Suleyman (Taylor & Francis Ltd, 2020)
Rheum ribes L. (rhubarb) is belonging to Polygonaceae, and its roots and fresh shoots are consumed as vegetable in Turkey. This plant is considered to be one of the most important pharmaceutical raw materials in Middle East. In this study, the antiradical, antimicrobial, cytotoxic and bioactive properties of water, ethanol, and methanol extracts of R. ribes stems were determined. R. ribes stems water, ethanol and methanol extracts are better scavenged ABTS(center dot+) (99.27, 99.91, and 99.88%), DPPH center dot (83.11, 81.42, and 83.26%), and OH center dot radicals (93.49, 94.21, 95.86%) than standard antioxidant BHA (95.32, 80.49, and 93.78%). Stems of R. ribes abundantly include bioactive compounds, dominated by rutin, catechin, caffeic acid, ferulic acid, alpha-tocopherol and vitamin D. These extracts show effective cytotoxic properties against PC-3, A2780, HCT-116 and MCF-7 cancer cell lines at 24h. It is found that R. ribes contain high amount important bioactive contents, and has effective antiradical and cytotoxic properties.
Keywords: Rhubarb; antiradical; antimicrobial; cytotoxicity; phytosterol